Associated factors of stress, urgency, and mixed urinary incontinence in a geriatric outpatient assessment of older women with hip fracture - Hellman-Bronstein, Aino T.; Luukkaala, Tiina H.; Ala-Nissilä, Seija S.; Nuotio, Maria S. (Springer, 2025)
Purpose Urinary incontinence (UI) is known to be common among older female hip fracture patients. Little is known about different subtypes of UI among these patients. Our aim was to identify factors associated with subtypes of UI in a cross-sectional design.
Methods 1,675 female patients aged ≥ 65 and treated for their first hip fracture in Seinäjoki Central Hospital, Finland, during 2007–2019, were included in a prospective cohort study. Of these, 1,106 underwent comprehensive geriatric assessment (CGA), including questions on continence, at our geriatric outpatient clinic 6 month post-fracture. A multivariable-adjusted multinomial logistic regression model was used to examine factors associated with UI subtypes.
Results Of the 779 patients included, 360 (46%) were continent and 419 (54%) had UI 6-month post-fracture. Of the women with UI, 117 (28%) had stress UI, 183 (44%) had urgency UI and 119 (28%) had mixed UI, respectively. Mean age of the patients was 82 ± 6,91. In multivariable analysis, depressive mood and poor mobility and functional ability were independently associated with stress UI. Fecal incontinence (FI) and Body Mass Index (BMI) over 28 were independently associated with urgency UI. Mixed UI shared the aforementioned factors with stress and urgency UI and was independently associated with constipation.
Conclusions Mixed UI was associated with most factors, of which depressive mood and impaired mobility and poor functional ability were shared with stress UI, and FI and higher BMI with urgency UI. CGA is key in assessing UI in older hip fracture patients, regardless of subtype.